Calculation of Schmid factor in Mg alloys: Influence of stress state. (October 2019) - Xia, Dabiao; Chen, Xiang; Huang, Guangsheng; Jiang, Bin; Tang, Aitao; Yang, Hong; Gavras, Serge; Huang, Yuanding; Hort, Norbert; Pan, Fusheng
Abstract: A modified global Schmid factor under different stress states was developed by introducing the stress intensity to normalize the stress tensor. The new method offers an efficient way to compare the activation of one deformation mode under different stress states. The distributions of global Schmid factors for deformation modes in Mg alloys were also studied using this new method. The results indicated that stress state dominated the distributions of global Schmid factors for different deformation modes in a similar way. Additionally, the deformation compatibilities among deformation modes were also influenced by the stress state, especially under a biaxial stress state. Graphical abstract: Unlabelled Image